Sosial Media Influencer : Trust, Engagement, dan Credibility Terhadap Keputusan Pembelian Produk Kosmetik Merek Lokal Pada Generasi Milenial di Banjarmasin - Adista Anjar Diany; Rika Yuliyanti (Komunitas Dosen Indonesia, 2025)
The remarkable advancement of social media technologies as a promotional platform has transformed influencers into key agents in shaping consumer behaviour, particularly noticeable among Millennials and Generation Z. In Indonesia, the rise of local cosmetic brands has been closely tied to the effectiveness of influencer marketing strategies in building consumer trust and engagement. This research seeks to examine how trust, engagement, and credibility of social media influencers affect the purchase decisions of Millennial consumers toward local cosmetic products in Banjarmasin. A quantitative research approach was employed using a non-probability sampling technique, specifically purposive sampling. The study involved 290 Millennial respondents in Banjarmasin who had previously purchased local cosmetic products based on influencer recommendations. This study utilized an online questionnaire for data collection, and the obtained data were analyzed using the PLS approach through SmartPLS version 3.0. The study concludes that building consumer trust and fostering active engagement between influencers and audiences are crucial strategies for enhancing purchase intentions toward local cosmetic brands. This highlights the importance of authenticity and emotional connection in influencer marketing for targeting Millennial consumers.